2017
DOI: 10.3389/fphar.2017.00221
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Apelin/APJ System in the Regulation of Liver Disease

Abstract: Apelin is an endogenous peptide that is a ligand for the APJ receptor (angiotensin II receptor like-1, AT-1). The apelin/APJ system is distributed in diverse periphery organ tissues. It has been shown that the apelin/APJ system plays various roles in physiology and pathophysiology of many organs. It regulates cardiovascular development or cardiac disease, glycometabolism and fat metabolism as well as metabolic disease. The apelin/APJ system participates in various cell activities such as proliferation, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
(53 reference statements)
1
27
0
Order By: Relevance
“…oxysporum , which is detected in the extract. Glp 1- Apelinendogenous peptide capable of binding the apelin receptor (APJ), which was originally described as an orphan G-protein-coupled receptor widely expressed in the tissues of human organs [73]. The apelin is so far not reported in plant systems which need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…oxysporum , which is detected in the extract. Glp 1- Apelinendogenous peptide capable of binding the apelin receptor (APJ), which was originally described as an orphan G-protein-coupled receptor widely expressed in the tissues of human organs [73]. The apelin is so far not reported in plant systems which need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, apelin played pivotal and various roles in the physiological and pathophysiological processes, including regulation of blood pressure, cardiac contractility, angiogenesis, metabolic balance, cell proliferation, apoptosis, and inflammation [912]. In addition, it has been shown that in the liver, apelin participated in hepatocyte apoptosis, glycogen synthesis, and fibrosis formation [13, 14]. A recent clinical investigation reported that serum apelin was associated with the histological and hemodynamic states of chronic liver disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the apelin-APJ axis promotes liver inflammation and fibrosis mainly through elevated expression of collagen-II and platelet-derived growth factor receptor β (PDGFRβ) that can explain rather detrimental then protective role of apelin over- expression found in the present study [26]. In the liver, the apelin/APJ system may participate in the formation of hepatic fibrosis or cirrhosis by inhibiting liver regeneration and promoting Fas-induced apoptosis [27]. Nonetheless, anti-apoptotic effects of apelin on vascular smooth muscle cells have also been observed [28].…”
Section: Resultsmentioning
confidence: 52%